IMPROVING THE TRAINING MECHANISM WITH DEEPENING OF PEDAGOGICAL SCIENCES IN PRIMARY AND PRESCHOOL EDUCATION - Karimjonov A.; Karimjonova D. A. (Galaxy International Interdisciplinary Research Journal, 2023)
In the article, based on the requirements of the current era, measures to improve the mechanism of training highly qualified specialists, i.e. high-potential pedagogues in primary and preschool educational organizations and training them in depth of knowledge, skills and qualifications in subjects, are reflected, in particular, high-quality pedagogues based on the "Development Strategy of New Uzbekistan" great attention is paid to the issue of personnel training.